Ambubagging as a therapeutic technique: Clinical guidelines - M. Barker; C. J. Eales (AOSIS, 1994)
A review of the literature relating to ambubagging was undertaken. During the period 1980-1992, several studies that were done investigated a scientific basis for the use of bagging and conflicting evidence was found. This may have been due to discrepancies in the measuring tools used as well as the divergence of the research designs by the investigators. Guidelines for the effective use of ambubagging as a therapeutic technique are set out.